Data density and poor organization: analyzing the performance and Attentional effects of two aspects of display clutter. (September 2015) - Moacdieh, Nadine; Sarter, Nadine
Display clutter has been shown to lead to breakdowns in attention and performance during visual search in data-rich domains. However, the contribution of, and interaction between, the two key aspects of clutter - data density and poor organization - are not well understood. The aim of this study was to fill this gap by systematically varying both factors and collecting performance and eye tracking data. This data was then used to analyze the performance and underlying attentional costs resulting from the two aspects of clutter. Participants performed visual search tasks in a simulated graphics program. Data density (density of icons) and display organization (grouping of icons) were manipulated. The dependent measures were response time, error rate, eye movements, and subjective clutter ratings. Results confirmed the negative effects of high data density and poor organization on response time and error rate. More importantly, eye tracking metrics reflected the effects of data density and organization on attention allocation and helped explain the observed performance decrements. In particular, spatial density mirrored the interaction effects between data and organization, and the nearest neighbor index (NNI) helped differentiate between the effects of high data density and poor organization. These findings suggest that eye tracking is a powerful means of obtaining a more detailed understanding of the effects of clutter and may also prove useful for real-time detection of clutter.